Nakama: Reception on the Audience of One Piece Anime by Eiichiro Oda - Mery Kharismawati; Lufi Wahidati (ProTVF, 2023)
Background: The theme of friendship in anime is often why an anime fan makes an anime title his/ her favorite. One Piece by Eiichiro Oda is an anime themed on the friendship of pirate crews. It aired on Indonesia’s private television station in the 2000s. In One Piece, the word “Nakama” is assumed to represent the sincere bonds of friendship offered by the character Luffy. But there’s also an assumption about the hidden meaning of making someone into their nakama. Not the one celebrated by the fans, but a reciprocal deed of a human being who needs another person’s help to reach their ambition. The assumption is up because One Piece fan who was touched by this character’s charisma also called themselves “Nakama.” Purpose: Find out the dominant, negotiation, and opposition regarding the scene of “Nakama” explanation by the character Nami in anime episode 102. Methods: This research used a qualitative method with a reception analysis approach by Stuart Hall. An in-depth interview was conducted with four informants who had been fans of One Piece since childhood and studied Japanese language and culture. Results: This research revealed that “nakama” has a biased meaning and does not only refer to “sincere friendship .”The informant’s answers were also influenced by their knowledge of Japanese culture learned in college and their everyday socializing experiences. Two informants are in the dominant hegemony position, and the rest are in a negotiation position because they have not found someone like “nakama” in the One Piece anime. Implications: Provide information about how the audience learning the Japanese language and culture view the meaning of “nakama” in their favorite anime and their view about friendship in real life.